A contactless human vital sign monitoring system using a Doppler radar - Yong, Qi; Zhao, Yifan (Elsevier, 2025)
Traditional vital signs monitoring methods are associated with certain limitations, such as requiring direct skin contact, causing potential distractions from sensors, and being susceptibility to electromagnetic interferences. Non-contact measurement methods have attracted growing interest but existing solutions face challenges in terms of working distance, accuracy, lack of temporal resolution, and applications in real-time heartbeat detection. This study introduces a novel non-contact vital sign monitoring system based on a K-band radar with dedicated algorithms for demodulation, parametric filter design, and self-adapting real-time heartbeat detection and extraction. This system provides precise and reliable per-beat heartrate detection and measurement, under a wide range of distances and working conditions, achieving superior performances and functionalities compared to existing contact-based implementations. By comparing with photoplethysmography and phonocardiogram sensors, the proposed system achieved real-time accurate per-beat heart rate measurement, with a relative root mean squared error of < 5 % for working distance of up to 3.2 m. Additionally, it can detect apneas and abnormal breathing activities, while also generating phonocardiogram and vibrography signals as a contactless virtual stethoscope. We anticipate that the solution will enable a wide range of applications including critical personnel monitoring, home and healthcare surveillance, self-assisted public health devices, and rescue operations.
Keywords: Biomedical Engineering; 3006 Food sciences; Contactless; Vital signs; Doppler radar; Parametric filter designing; Digital signal processing